PENGARUH MODEL PEMBELAJARAN THINK TALK WRITE (TTW) TERHADAP HASIL BELAJAR BAHASA INDONESIA - Safara, Safara Rodifah Abrori; Chairul Amriyah (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2025)
This study aims to determine the effect of the Think Talk Write (TTW) learning model on the learning outcomes of Indonesian language of grade V students of SD Negeri 1 Rajabasa Lampung. The research method used is a quantitative experiment with a one-group pretest post-test design. The subjects of the study were grade V students and data collection was carried out through observation, documentation and student performance techniques. The researcher used descriptive and inferential statistical analysis techniques. The results of the hypothesis test showed that the t count value > t table, so the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Thus, the researcher concluded that the application of the Think Talk Write (TTW) learning model had a positive effect on the learning outcomes of Indonesian language of grade V students of SD Negeri 1 Rajabasa.